Diagnostic-therapeutic algorithm of patients with combined atherosclerotic lesions of coronary and brachiocephalic arteries - O. Y. Usenko; A. V. Gabrielyan; P. I. Nikulnikov; V. V. Beleyovych; A. V. Ratushnyuk; О. Y. Pelepas (Ukrainian Journal of Cardiovascular Surgery, 2017)
By combined atherosclerotic lesions of several arterial basins there is no single approach to fulfill simultaneous or staged interventions. The algorithm for decision making as to surgical approach by multifocal atherosclerosis remains the subject of debate.Objective: to improve the results of treatment of patients with combined atherosclerotic occlusive lesions of coronary and carotid arteries by development and implementation of an diagnostic -therapeutic algorithm.Materials and methods: the analysis of the results of surgical treatment of 63 patients with multifocally atherosclerosis has been carried out. The examination record included general clinical and special methods: electrocardiography, echoencepha-lography, cardiography, coronaroventriculography, duplex sonography of carotid arteries, perfusion computer tomography of the brain.Results and their discussion. By circulatory decompensation in both arterial basins, which not allowed performing the circulation management in one of vascular basin, and simultaneous operations using neuromonitoring was not accompanied by an increased risk of ischemic neurologic and cardiac complications. When was stable run of atherosclerotic cardiovascu-lar disease and without neurological symptoms the stage approach allowed us to obtain good or satisfactory results bymost patients.Conclusion. To determine the phasing by combined lesions of carotid and coronary arteries we have proposed scientif-ically-based algorithm of actions. Simultaneous operations are shown by patients with risk of circulatory decompensation by intervention in one of the vascular basin. A staged approach can be used by stable run of atherosclerotic cardiovascular disease and without clinically significant neurological symptoms.